2022
DOI: 10.1212/wnl.0000000000013145
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Diagnosis of Stroke and Cardiovascular Conditions in Primary Care During the First 2 COVID-19 Waves in the Netherlands

Abstract: Background and objectivesAlthough there is evidence of disruption in acute cerebrovascular and cardiovascular care during the COVID-19 pandemic, its downstream effect in primary care is less clear. We investigated how the pandemic affected utilization of cerebrovascular and cardiovascular care in general practices (GPs) and determined changes in GP-recorded diagnoses of selected cerebrovascular and cardiovascular outcomes.MethodsFrom electronic health records of 166,929 primary care patients aged 30 or over wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…However, while a patient-centered survey by Schuster et al (22) revealed that the share of patient-initiated cancellations of primary care appointments was smaller than healthcare-initiated, only 37% of outpatient physicians surveyed in this study agreed that the decline could be traced back to the provider behavior, whereas 97% saw the cause in the changed patient behavior. Furthermore, recent studies support the thesis that the patient's behavior could be reasonable for the delay of outpatient service utilization regarding preventive care and visits for chronic diseases due to anxiety, reduced social activities, increased infection risk and a lack of perception of non-disabling symptoms (20,(23)(24)(25)(26). The surveyed physicians supported these indications, confirming (97%) reasons for declined disease recognition remain in changed patient behavior.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, while a patient-centered survey by Schuster et al (22) revealed that the share of patient-initiated cancellations of primary care appointments was smaller than healthcare-initiated, only 37% of outpatient physicians surveyed in this study agreed that the decline could be traced back to the provider behavior, whereas 97% saw the cause in the changed patient behavior. Furthermore, recent studies support the thesis that the patient's behavior could be reasonable for the delay of outpatient service utilization regarding preventive care and visits for chronic diseases due to anxiety, reduced social activities, increased infection risk and a lack of perception of non-disabling symptoms (20,(23)(24)(25)(26). The surveyed physicians supported these indications, confirming (97%) reasons for declined disease recognition remain in changed patient behavior.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have evaluated the impact of the early COVID-19 pandemic on primary care consultations, representing a dramatic decline ( 9 , 11 , 13 , 14 , 20 ). This analysis confirmed this decrease in outpatient consultations, especially at the beginning of the pandemic during the nationwide contact bans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many cardiovascular diseases are time-dependent. An overwhelmed and fully committed health care system in the fight against respiratory disease caused by the SARS-CoV-2 pandemic partially neglected time-dependent conditions (Fox et al 2022 ; Velek et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the widespread postponement of elective procedures and visits, coupled with anxiety about COVID-19 exposure, caused larger disruptions in care for people with chronic illnesses. 4 Velek et al 3 report age and sex differences, with people over 65 and women experiencing the largest declines in GP encounters, but they did not evaluate how social determinants of health (SDOH) may differentially affect GP consultations and new diagnoses. This could be due to relative homogeneity of the study population or unavailability of SDOH metrics.…”
mentioning
confidence: 99%
“…In this issue of Neurology ®, Velek and colleagues 3 published a study that starts to fill this gap by highlighting the inadvertent effects of the COVID-19 pandemic on the population-wide burden of cerebrovascular disease. Using electronic health records from 18% of the general practices (GPs) in the Rotterdam region in the Netherlands, the authors found that new diagnoses of stroke and TIA had declined by 29% and 37%, respectively, during the first pandemic wave (March–May 2020) compared to prepandemic derived expected counts.…”
mentioning
confidence: 99%